204 Simvastatin in Aneurysmal Subarachnoid Haemorrhage (STASH) Trial: A Clinical Phase 111 Randomised Placebo Controlled Trial—The Results. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Turner, Carole L.; Smith, Christopher; Murray, Gordon D.; Hutchinson, Peter J.; Kirkpatrick, Peter J.
Abstract: INTRODUCTION: Prevention of cerebral vasospasm is the target of modern drug therapy, candidates of which include statins. The results of phase 11 studies have shown promise in this arena. STASH is an international multicentre randomised controlled phase 111 trial designed to assess the effects of Simvastatin 40 mg on the long and short term outcome of patients who have suffered from an acute aneurysmal subarachnoid haemorrhage (SAH). METHODS: All grades of SAH patients with a radiological proven aneurysm were eligible. Patients were randomized to receive Simvastatin 40 mg or placebo for up to 21 days. Primary outcome was the modified Rankin Disability Score (mRS) at 6 months. Secondary outcome measures included the SF-36 short form questionnaire at 6 months, the incidence and duration of delayed ischemic deficit (DID) and associated rescue therapy, the incidence and severity of sepsis, length of intensive care and total acute hospital stay, and discharge destination. Primary analysis was an ordinal regression of the mRS following the intention to treat (ITT) principle. RESULTS: Eight hundred three patients (252 male, 551 female) were recruited with mean age 50 years (range 21 67). Six hundred seventy-six (85%) from UK centres and 127 (15%) from non-UK centres. Five hundred eighty-eight patients (73%) were WFNS grade 1-2 on admission and 84% had a CT scan Fisher Grade 3 or 4. Five hundred fifteen patients (64%) were coiled. 6 month outcome data is available for 782 (97%) of which 560 (72%) were mRS 0-2 at 6 months. DID was confirmed in 131 (16.3%), and the overall mortality at 6 months was 9% (n = 72). Mean length of hospital stay was 20 days and ITU stay 12 days. Four hundred seventy-one (59%) were discharged directly home and 102 (13%) were discharged to rehabilitation centres. CONCLUSION: Primary outcome, secondary outcome measures and subgroup analyses will be presented from the ITT population.